Answer:
Answer: the equation is y'=
![(3)/(2)x'-11](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rkhgr0mk3xkdx2xkkdlsitxwbp6roetun3.png)
Explanation:
A line is given whose equation is given as
------(1)
and we have to find the equation of another line which is perpendicular to this.
Let the equation of the line be y'=mx'+c------(2)
This line passes through a point (8,1) so we put the values of x & y in the equation.
⇒ 1 = m×8+c
⇒ 8m+c = 1------(3)
We know that if two lines are perpendicular to each other then multiplication of their slopes is equal to (-1).
Therefore m×
=(-1)
⇒
![(2)/(3) m=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/qk5jagsaxabomyjiprzse6bpuvji88q7fw.png)
⇒m=
![(3)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/85tww783zdtzzps1k74cyql3cl3s1y42ha.png)
Now we put the value of m in equation (3) to get the value of c
8×
+c = 1
12+c=1
c = (-11)
Therefore the equation will be y'=
![(3)/(2)x'+(-11)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/r65fpypnhmtw8xqtknq1nizjfejkfikdv4.png)